How Much Yield Is Needed to Offset the Cost of Injecting Trees With Oxytetracycline? - Singerman, Ariel (EDIS, 2023)
Citrus growers in Florida are now allowed to inject their trees with oxytetracycline to try to control CandidatusLiberibacter asiaticus (CLAS) and/or suppress Huanglongbing (HLB, citrus greening). The use of oxytetracycline is expected to reduce the titer (i.e.: presence and amount within the tree) of the bacteria Candidatus Liberibacter asiaticus within HLB-affected trees, which, in turn is expected to improve the trees’ condition and, ultimately, increase yield. In this article, we use cost estimates to address the question of how much of a yield response would be needed for the treatment to be economically viable, which can be useful for Florida citrus growers to decide whether to adopt the treatment.